Normering og deskription i Den Danske Ordbog – mere eller mindre? - Trap-Jensen, Lars (LexicoNordica, 2002)
As a corpusbased dictionary, The Danish Dictionary has constantly during its compilation been confronted with the gap between the norm of the standard language and the variability of language use observed in natural texts. In this article, the problems involved are discussed in relation to four selected areas where the difficulties are particularly pronounced: orthography, inflection, meaning and lemma selection. Editorial considerations as well as lexicographic examples are discussed, and possible solutions are suggested that try to balance the need for uniformity and recommendations of the dictionary user, on the one hand, with the diversity of the linguistic reality that serves as the descriptive basis of the dictionary, on the other.